CD11c.DTR mice develop a fatal fulminant myocarditis after local or systemic treatment with diphtheria toxin. Issue 8 (8th June 2016) - Männ, Linda; Kochupurakkal, Nora; Martin, Christian; Verjans, Eva; Klingberg, Anika; Sody, Simon; Kraus, Andreas; Dalimot, Jill; Bergmüller, Eileen; Jung, Steffen; Voortman, Sylvia; Winterhager, Elke; et al.
Abstract : The transgenic CD11c.DTR mouse strain is a frequently used animal model to study effects of CD11c‐specific cell ablation. We here show that a local or systemic treatment of these mice with the cell depletion trigger diphtheria toxin ultimately leads to the development of a fatal fulminant myocarditis. Abstract : To assess the role of alveolar macrophages (AMs) during a pulmonary Aspergillus fumigatus infection AMs were depleted by intratracheal application of diphtheria toxin (DTX) to transgenic CD11c.DTR mice prior to fungal infection. Unexpectedly, all CD11c.DTR mice treated with DTX died within 4–5 days, whether being infected with A. fumigatus or not. Despite measurable impact of DTX on lung functional parameters, these constrictions could not explain the high mortality rate. Instead, DTX‐treated CD11c.DTR animals developed fulminant myocarditis (FM) characterized by massive leukocyte infiltration and myocardial cell destruction, including central parts of the heart's stimulus transmission system. In fact, standard limb lead ECG recordings of diseased but not healthy mice showed a "Brugada"‐like pattern with an abnormally high ST segment pointing to enhanced susceptibility for potential lethal arrhythmias. While CD11c.DTR mice are extensively used for the characterization of CD11c + cells, including dendritic cells, several studies have already mentioned adverse side effects following DTX treatment. Our results demonstrate that this limitation is based on severe myocarditis but not on the expected lung constrictions, and has to be taken into consideration if this animal model is used. Based on these properties, however, the CD11c.DTR mouse might serve as useful animal model for FM.